Evaluating Self-Produced PLA Filament for Sustainable 3D Printing: Mechanical Properties and Energy Consumption Compared to Commercial Alternatives - Luca Fontana; Paolo Minetola; Mankirat Singh Khandpur; Alberto Giubilini (Journal of Manufacturing and Materials Processing)
This study investigates the feasibility of self-producing polylactic acid (PLA) filament for use in 3D printing. The filament was fabricated using a desktop single-screw extruder and evaluated against commercially available PLA in terms of mechanical properties and energy consumption. Specimens were printed at two layer heights (0.2 mm and 0.3 mm) and four infill densities (25%, 50%, 75%, and 100%). The self-produced filament exhibited lower diameter precision (1.67 ± 0.21 mm), which resulted in mass variability up to three orders of magnitude higher than that of the commercial filament. Thermal analysis confirmed that the extrusion and printing process did not significantly alter the thermal properties of PLA. Mechanical testing revealed that a layer height 0.3 mm consistently yielded higher stiffness and tensile strength in all samples. When normalized by mass, the specimens printed with commercial filament demonstrated approximately double the ultimate tensile strength compared to those that used self-produced filament. The energy consumption analysis indicated that a 0.3 mm layer height improved printing efficiency, cutting specific energy consumption by approximately 50% and increasing the material deposition rate proportionally. However, the total energy required to print with self-produced filament was nearly three times higher than that for commercial filament, primarily due to material waste that stems from inconsistencies in the diameter of the filament. These findings are significant in evaluating the practicality of self-produced PLA filament, particularly in terms of mechanical performance and energy efficiency.